2020
DOI: 10.3390/brainsci10060387
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Cognitive Electrophysiological Differences in the Executive Functions of Taiwanese Basketball Players as a Function of Playing Position

Abstract: The effect of the predominant playing position of elite basketball players on executive functions using both behavioral and electrophysiological measurements was investigated in the present study. Forty-six elite basketball players, including 27 guards and 19 forwards, were recruited. Event-related potential (ERP) signals were simultaneously recorded when the athletes performed the visual Go/NoGo task. Analyses of the results revealed that the guards and forwards groups exhibited comparable behavioral (i.e., r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For this study, a sport-specific task with video footage of table tennis situations was designed, as we think that this task is best suited to capture the inhibition processes trained by table tennis players. Actually, a gap exists in the literature, as most studies used nonecological tasks to evaluate IC in expert populations 18 , 19 , 26 , 67 . One exception is the study by Muraskin et al 17 , who compared baseball players to baseball novices with a Go/NoGo task reflecting real scenarios of simulated baseball trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, a sport-specific task with video footage of table tennis situations was designed, as we think that this task is best suited to capture the inhibition processes trained by table tennis players. Actually, a gap exists in the literature, as most studies used nonecological tasks to evaluate IC in expert populations 18 , 19 , 26 , 67 . One exception is the study by Muraskin et al 17 , who compared baseball players to baseball novices with a Go/NoGo task reflecting real scenarios of simulated baseball trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of basketball, a high level of concentration is necessary to ensure rhythmic follow-through while dribbling the ball. Also, basketball as an open skill requires participants to perform in a dynamic environment and respond to unpredictable and frequent environmental changes throughout the activity (Dai et al, 2013;Chiu et al, 2020;Ke et al, 2021). Therefore, basketball training will engage children in quickly evaluating all possible situations to choose a preferred strategy and switching technical actions when necessary (Pedro et al, 2021), it is possible that increasing the frequency of basketball training allows children to practice their cognitive flexibility (Nuri et al, 2013).…”
Section: Switching Taskmentioning
confidence: 99%
“…Those could be different for players in different playing positions. Chiu et al 15 found that although the guards and forwards exhibited similar abilities in terms of behavioral inhibition, different neural processing efficiencies still exist in the basketball playing positions, with guards showing divergent efficiencies in the target evaluation and response selection of the target and non-target stimuli and fewer cognitive resources during premotor preparation and decision-making as compared to the forwards. Zhai et al 16 explored the differences in technical performances of players considering playing positions by controlling the effect of situational variables in each International basketball federation (FIBA) female continental basketball competition.…”
Section: Introductionmentioning
confidence: 99%